Fluid and carbohydrate intake during team games - Burke, L. M. (Sportscience, 1999)
The effects of nutritional strategies on performance in team games are uncertain, because changes in performance are hard to measure accurately in these sports. A small number of researchers have used lab tests, simulated games, or real games to measure the effect of hydration status and carbohydrate feeding on simulated game performance. The lack of consistency in the outcomes of these studies may be due to lack of precision in the measurement of performance, differences between athletes or sports in the effects of the nutritional intervention, or differences in environmental conditions between studies. Until there are better research tools, those who work with team-sport athletes should continue to give nutritional advice based on research with endurance athletes. However, the fluid and energy requirements in a team game may differ considerably from those of an endurance event, so the advice should be tempered by common sense and experience. The factors affecting fluid balance in team sports are shown.